2020
DOI: 10.1007/s41918-020-00075-2
|View full text |Cite
|
Sign up to set email alerts
|

Latest Advances in High-Voltage and High-Energy-Density Aqueous Rechargeable Batteries

Abstract: Aqueous rechargeable batteries (ARBs) have become a lively research theme due to their advantages of low cost, safety, environmental friendliness, and easy manufacturing. However, since its inception, the aqueous solution energy storage system has always faced some problems, which hinders its development, such as the narrow electrochemical stability window of water, poor percolation of electrode materials, and low energy density. In recent years, to overcome the shortcomings of the aqueous solution-based energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(59 citation statements)
references
References 143 publications
(134 reference statements)
0
57
0
Order By: Relevance
“…Some recent reviews have summarized strategies for widening the device voltage window in dilute electrolytes, such as employing neutral electrolytes and establishing artificial SEI. [48,49] For example, a lithium superionic conductor film with the ionic conductivity of ≈0.1 mS cm −1 designed by Wu et al was used to expand the operating window of Li metal battery by covering on the lithium metal negative electrode. [50] www.afm-journal.de www.advancedsciencenews.com…”
Section: (9 Of 23)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent reviews have summarized strategies for widening the device voltage window in dilute electrolytes, such as employing neutral electrolytes and establishing artificial SEI. [48,49] For example, a lithium superionic conductor film with the ionic conductivity of ≈0.1 mS cm −1 designed by Wu et al was used to expand the operating window of Li metal battery by covering on the lithium metal negative electrode. [50] www.afm-journal.de www.advancedsciencenews.com…”
Section: (9 Of 23)mentioning
confidence: 99%
“…[38] The SEI film can be formed through the solvolysis, and by introducing additives as well. [48,57] A work has reported that a solid interphase composed of organic fluorinated hydrocarbon and inorganic fluorides, generated from the LiTFSI-HFE (highly fluorinated ether) gel, and the Li-ion battery based on a (LiBr) 0.5 (LiCl) 0.5 -graphite cathode and HFE gel graphite anode delivered an energy density of 460 Wh kg −1 . [58] Although the graphite anode can store energy effectively, the low working potential of the graphite anode and the corresponding lithium coating hinder the rapid charge and discharge of the battery.…”
Section: (12 Of 23)mentioning
confidence: 99%
“…The composition is favorable for ion transport in the SEI. As Li 2 CO 3 has high conductivity, an ultra‐high concentration carrier region is generated at the interface between Li 2 CO 3 and LiF, which can act as the channel for fast transport of Li + ions [48] . Additionally, the presence of high‐concentration salt promises the stability of the formed SEI during long‐term cycling in WIS electrolytes.…”
Section: Working Mechanisms Of Wismentioning
confidence: 99%
“…The conventional Li‐ion batteries as well as the emerging Na‐ion and K‐ion batteries operate in organic carbonate solutions with fluoro‐containing salts, which poses severe environmental risks associated with thermal runaway, corrosive hydrolysis, limited bioremediation [1] . Aqueous metal‐ion batteries compensate for these shortcomings at a cost of reduced energy density, yet offer superior cycle life and high power characteristics, outperforming the organic intercalation‐based batteries in terms of fast charging capabilities [2] . Exceptional power density as well as impressive cycling stability is well documented for Prussian blue analogues (PBA) in aqueous Na‐ion and K‐ion batteries [3–9] .…”
Section: Introductionmentioning
confidence: 99%